Survival Benefit of Pyloric Lymph Node Dissection for Siewert Type II/III Adenocarcinoma of the Esophagogastric Junction Based on Tumor Diameter: A Large Cohort Study - Lin, Xia; Li, Zhengyan; Tan, Chenjun; Ye, Xiaoshuang; Xiong, Jie; Liu, Jiajia; Mo, Ao; Shi, Yan; Qian, Feng; Yu, Peiwu; Zhao, Yongliang (Frontiers in Oncology, 2021)
Background It is unclear whether the dissection of pyloric lymph nodes (PLNs, No.5 and No.6 lymph nodes) is necessary for AEG (Adenocarcinoma of the Esophagogastric Junction) with a tumor diameter >4 cm based on current guidelines. The purpose of this study was to investigate whether pyloric node lymphadenectomy is essential for patients with Siewert type II and III AEG according to different tumor diameters. Methods This study included 300 patients with Siewert type II/III AEG who underwent a transabdominal total gastrectomy at a high-volume center in China from January 2006 to December 2015. We used the index of estimated benefit from lymph node dissection (IEBLD) to analyze the efficacy of pyloric lymphadenectomy. Results In Siewert type II AEG, no significant differences were observed in 5-year overall survival (OS) between patients with PLN-positive cancer and patients with stage III AEG without PLN metastasis (23.1% vs 30.6%, P=0.505). However, in Siewert type III AEG, the OS of patients with PLN-positive cancer was significantly lower than that of patients with stage III without PLN metastasis (7.9% vs 27.8%, P=0.021). According to the IEBLD, the dissection of PLNs did not appear to be beneficial in either Siewert type II AEG or type III AEG, whereas a stratified analysis revealed that PLN dissection yielded a high therapeutic benefit for Siewert type II AEG with tumor diameters >4 cm. Conclusion We recommended that the PLNs be dissected in patients with Siewert type II AEG with a tumor diameter >4 cm. Total gastrectomy should be selected as a standard treatment for Siewert type II AEG with a tumor diameter >4 cm and Siewert type III AEG.